Complicaciones maternas y perinatales asociadas a ruptura prematura de membranas pretérmino en el Hospital León Becerra Camacho, Milagro – 2017 - Paredes Pallo, Danilo Gabriel (2018)
Background: Preterm rupture of preterm membranes occurs in 10% of pregnancies, is associated with 30 and 40% of cases of prematurity. This pathology is one of the obstetric complications with high levels of incidence. Objective: To identify the maternal and perinatal complications associated with premature rupture of preterm membranes in León Becerra Camacho Hospital, Milagro - 2017. Methodology: It is deductive because it was based on the data collected from the statistical department, the modality was quantitative, descriptive, bibliographic and basic non-experimental. Results: The prevalence of premature rupture of membranes is caused by a lack of prenatal controls in pregnancy, recurrent infections of the urinary tract and poor hygiene. Conclusions: Maternal and perinatal complications are associated with premature rupture of membranes due to insufficient controls of pregnancy, recurrent urinary tract infections and gynecological-obstetric history